2010
DOI: 10.1007/s00115-009-2922-y
|View full text |Cite
|
Sign up to set email alerts
|

Tabakkonsum bei Erwachsenen mit ADHS

Abstract: Zusammenfassung HintergrundUntersuchungen aus den USA wiesen Zusammenhänge zwischen der Aufmerksamkeitsdefizit-/Hyperaktivitätsstörung (ADHS) und dem Rauchen nach. Bis anhin wurden in der Schweiz keine vergleichbaren Studien durchgeführt. Ziel der vorliegenden Arbeit war es, neue Erkenntnisse über die Beziehung der ADHS und dem Tabakkonsum bei erwachsenen ADHS-Patienten aus der Schweiz zu gewinnen. Material und MethodenEine schriftliche Befragung zum Tabakkonsum and smoking behaviour; however, no specific wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…Our findings were based upon complete data from 100 adult ADHD patients. In this study, which is only published in German, we reported a significantly elevated rate of current smokers in our sample (55%), as compared to 31% in the general Swiss population [13]. …”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our findings were based upon complete data from 100 adult ADHD patients. In this study, which is only published in German, we reported a significantly elevated rate of current smokers in our sample (55%), as compared to 31% in the general Swiss population [13]. …”
Section: Introductionmentioning
confidence: 67%
“…We recruited 12 participants from a larger epidemiological study of 134 adult patients with ADHD who had presented to the ADHD consultation service at the Centre for Addiction Disorders, an outpatient facility of the Zurich University Hospital, Switzerland [13,48]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of all consecutive referrals to the ADHD consultation service of the Zurich University Psychiatric Hospital 26 between 2002 and 2011, we included adults with a confirmed diagnosis of ADHD and with available information on substance use (N=413). There were no other inclusion or exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, drug abuse was significantly more prevalent over those suffering from ADHD than the control group [6]. Adults suffering from ADHD start nicotine consumption at lower ages, indicate higher levels of nicotine addiction And have more problems in continuing their smoking quit term [7]. In recent years, methamphetamine (glass) abuse has been increasing in Iran, especially over the young population, with the abuse of this stimulus substance bringing about lots of personal and socio-economic consequences [8][9][10].…”
Section: Introductionmentioning
confidence: 99%